2011
DOI: 10.1161/circulationaha.110.978593
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Outcomes of Liberal Versus Selective Drug-Eluting Stent Use

Abstract: Background-Although the benefits of drug-eluting stents (DES) for reducing restenosis after percutaneous coronary intervention are well established, the impact of alternative rates of DES use on population-level outcomes is unknown. One-year rates of death or myocardial infarction were similar in both eras. Over this time period, the incidence of target lesion revascularization increased from 4.1% to 5.1%, an absolute increase of 1.0% (95% confidence interval, 0.1 to 1.9; Pϭ0.03), whereas total cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…An IV is an observable factor that is associated with a specific treatment pattern but is otherwise unrelated to underlying patient characteristics and does not directly affect the outcome of interest. Based on our previous work in the EVENT registry, 25 , whereas most other patient and treatment characteristics were similar over time. In this study, we used Cox proportional hazards models to validate the assumption that the enrollment year was not associated with differences in either mortality or TLR, independent of DES use.…”
Section: Discussionmentioning
confidence: 99%
“…An IV is an observable factor that is associated with a specific treatment pattern but is otherwise unrelated to underlying patient characteristics and does not directly affect the outcome of interest. Based on our previous work in the EVENT registry, 25 , whereas most other patient and treatment characteristics were similar over time. In this study, we used Cox proportional hazards models to validate the assumption that the enrollment year was not associated with differences in either mortality or TLR, independent of DES use.…”
Section: Discussionmentioning
confidence: 99%
“…68,69 Reducing the use of drug-eluting stents among patients at low risk for restenosis may result in cost savings with a small effect on the rate of repeat revascularization. 69,70 However, reimbursement systems vary widely, rendering cost-effectiveness analyses rarely applicable to different health care systems. In the United States, a reduction in the use of drug-eluting stents in 2007, as compared with a more liberal use of such stents in the period from 2004 through 2006 (in 68% and 92% of procedures, respectively), was associated with a small increase in the risk of repeat revascularization (4.1 to 5.1%) and a modest reduction in costs ($400 per patient) over a period of 1 year.…”
Section: Os T-effec T I V Ene Ssmentioning
confidence: 99%
“…2 A subanalysis on the multicenter Evaluation of Drug Eluting Stents and Ischemic Events (EVENT) registry concluded that the selective use of DES is a better cost-effective approach compared with unrestricted DES use. 3 Furthermore, it might be more reasonable to use BMS in patients with questionable compliance or concern on prolonged dual antiplatelet therapy, such as patients who might require noncardiac surgeries in the future.…”
Section: To the Editormentioning
confidence: 99%